Strong Coupling Constants of Negative Parity Heavy Baryons with π and K Mesons. (10th December 2017) - Aliev, T. M.; Bilmis, S.; Savci, M.
Abstract : The strong coupling constants of negative parity heavy baryons belonging to sextet and antitriplet representations of S U f ( 3 ) with light π and K mesons are estimated within the light cone QCD sum rules. It is observed that each class of the sextet-sextet, sextet-antitriplet, and antitriplet-antitriplet transitions can be described by only one corresponding function. The pollution arising from the positive to positive, positive to negative, and negative to positive parity baryons transitions is eliminated by constructing sum rules for different Lorentz structures. The obtained coupling constants are compared with the ones for the positive parity heavy baryons.